Otwieram sklep rzeźniczo-wędliniarski. (Malbork : [s.n.], 1947)
Afisz inf. o otwarciu sklepu w Malbroku 30.08.1947 r.
Keywords: Malbork (Polska) -- 1945-1970 -- druki ulotne; Malbork (Polska) -- 1945-1970 -- źródła